Edukasi Gizi sebagai Upaya Pencegahan Konstipasi pada Lansia di Desa Lamkawe Aceh Besar - Nunung Sri Mulyani; Dini Junita; Eva Fitriyaningsih; Arnisam Arnisam; Agus Hendra Al-Rahmad; Abdul Hadi (Jurnal Abdimas Kesehatan (JAK), 2022)
Constipation is a common problem and can cause serious problems. Constipation is a condition characterized by changes in the consistency of the stool to become hard, large in size, decreased in frequency or difficulty in defecation. Constipation is often characterized by symptoms of anxiety when defecation due to pain during defecation. Constipation can cause severe stress for sufferers due to discomfort. Another impact due to functional constipation is activity disturbances such as stomach cramps, decreased quality of life through decreased productivity. One of the prevention efforts is training and counseling the elderly regarding constipation. For this reason, the understanding of the elderly regarding constipation must be improved. This community service activity was carried out in the village of Lambawe. The implementation of this activity in September 2019. The target of this activity is the elderly. The method used in the implementation of this activity is the lecture and demonstration method. The results obtained in this activity are the target of understanding the material about constipation. It is suggested to the puskesmas to be able to work together in providing counseling related to education on constipation so that the elderly can understand the importance of preventing and overcoming constipation.